The relationship between political butterflying and political credibility - Rosal, Shirley C. (2001.)
This research attempts to find out whether a relationship exist between political butterflying and political credibility by using three intervening variables: the number of years in service of the politician, the number of programs and projects implemented and the political background of the politician.In the process of answering the said problem, the study also aimed for the following: (1) to find out if there is a relationship between number of years in service of the politician and political credibility, (2) to find out if there is a relationship between number of programs and projects of the politician and political credibility, and (3) to find out if there is a relationship between political background and political credibility. The study has three hypotheses which are the following: (1) there is a relationship between number of years in service of the politician and political credibility, (2) there is a relationship between the number of programs and projects of the politician and political credibility, and (3) there is a relationship between political background and political credibility. One hundred respondents from the total voting population of the town of Guimbal, Iloilo were chosen for the study manily those aging from 38-80 years old to ensure that they have voted in the 1980 election to the 1998 election. The data was obtained through one on one interview schedule with the respondents and was analyzed both qualitatively and quantitatively with the use of chi-square test, and simple frequency counts and percentages for some data. It was found that political butterflying does not directly affect the political credibility of the politician. The number of years in service of the politician, number of programs and projects implemented, and political background served as the qualifying factor determining the political credibility of the politician despite the fact that they switch parties during election.
Undergraduate Thesis (AB Political Science). -- Miagao, Iloilo : UPV-CAS, March 2001.